Analysis of faulted power systems - Anderson, P. M. (Paul M.) (IEEE Press power system engineering series., 1995)
This classic text offers you the key to understanding short circuits, open conductors and other problems relating to electric power systems that are subject to unbalanced conditions. Using the method of symmetrical components, acknowledged expert Paul M. Anderson provides comprehensive guidance for both finding solutions for faulted power systems and maintaining protective system applications. You'll learn to solve advanced problems, while gaining a thorough background in elementary configurations. Features you'll put to immediate use: Numerous examples and problems, clear, concise notation, analytical simplifications, Matrix methods applicable to digital computer technology, Extensive appendices.